The feasibility of using Apple's ResearchKit for recruitment and data collection: Considerations for mental health research - Bührmann, Leah; Van Daele, Tom; Rinn, Alina; De Witte, Nele A. J.; Lehr, Dirk; Aardoom, Jiska Joëlle; Loheide-Niesmann, Lisa; Smit, Jan; Riper, Heleen (Frontiers in Digital Health, 2022)
In 2015, Apple launched an open-source software framework called ResearchKit. ResearchKit provides an infrastructure for conducting remote, smartphone-based research trials through the means of Apple’s App Store. Such trials may have several advantages over conventional trial methods including the removal of geographic barriers, frequent assessments of participants in real-life settings, and increased inclusion of seldom-heard communities. The aim of the current study was to explore the feasibility of participant recruitment and the potential for data collection in the non-clinical population in a smartphone-based trial using ResearchKit. As a case example, an app called eMovit, a behavioural activation (BA) app with the aim of helping users to build healthy habits was used. The study was conducted over a 9-month period. Any iPhone user with access to the App Stores of The Netherlands, Belgium, and Germany could download the app and participate in the study. During the study period, the eMovit app was disseminated amongst potential users via social media posts (Twitter, Facebook, LinkedIn), paid social media advertisements (Facebook), digital newsletters and newspaper articles, blogposts and other websites. In total, 1788 individuals visited the eMovit landing page. A total of 144 visitors subsequently entered Apple’s App Store through that landing page. The eMovit product page was viewed 10327 times on the App Store. With 79 installs, eMovit showed a conversion rate of 0.76% from product view to install of the app. Of those 79 installs, 53 users indicated that they were interested to participate in the research study and 36 subsequently consented and completed the demographics and the participants quiz. From a technological point of view, the means provided by ResearchKit are well suited to be integrated into the app process and thus facilitate conducting smartphone-based studies. However, this study shows that only low recruitment rates were achieved with the dissemination strategies applied. We argue that smartphone-based trials require a well-designed app dissemination process to attain a sufficient sample size. Guidelines recommendations for smartphone-based trials will ensure the quality of these trials, facilitate researchers to do more testing of mental health apps and with that enlarge the evidence-base for mHealth.